KNOWLEDGE OF RISK FACTORS AND HEALTH IMPLICATIONS OF OBESITY AMONG WOMEN OF REPRODUCTIVE AGE IN IBADAN SOUTH-WEST LOCAL GOVERNMENT AREA, NIGERIA (2014)
Obesity is one of the non-communicable diseases (NCDs) of public health concern globally with negative impact on Reproductive Health (RH). Previous researches have shown that obesity is associated with other NCDs but there is dearth of information on the knowledge of the effect of obesity on RH among Women of Reproductive Age (WRA). This study was carried out to assess the knowledge of Risk Factors (RFs) and Health Implications (HIs) of obesity among WRA in Ibadan South-West Local Government Area. This was a descriptive cross-sectional study. Six Focus Group Discussion (FGD) sessions were conducted among WRA. A three-stage sampling technique was used, which included stratified random sampling technique using population density as a basis for stratification to proportionately select 500 WRA from six communities. Simple random technique was used to select a cluster each from the six communities while purposive sampling was used to select respondents from each cluster. Semi-structured, interviewer-administered questionnaire was used to elicit information on socio-demographic characteristics; knowledge of RFs assessed on a 12-point scale and scored low (≤7) and high (>7); also knowledge of HIs assessed on a 14-point scale and scored low (≤8) and high (>8). Obesity was assessed using Body Mass Index (BMI) and Waist-to-Hip Ratio (WHR). Respondents with BMI ≥30kg/m2 were classified as obese while those with WHR >0.85 had truncal obesity. Pattern of high calorie food consumption was assessed using food frequency questionnaire. The FGDs were analysed using thematic approach while the quantitative data were analysed using descriptive statistics, Chi-square and logistics regression tests at 5% level of significance. Most FGD participants disclosed that poor eating habits, heredity and being indolent could lead to obesity. Some were of the view that obesity has no HIs. Respondents‘ mean age was 29.9±8.7 years; 56.0% had tertiary education and 60.0% had ever given birth. Sixty-two percent had high knowledge of RFs for obesity while 13.2% had high knowledge of the associated HIs. Major RH problems associated with obesity mentioned by the respondents included infertility (34.4%) and obstructed labour (33.0%). Prevalence of obesity was 18.6% while 52.4% had truncal obesity. Frequently consumed high calorie foods include cocoa-based drinks (24.8%), soft drinks (19.6%) and snacks (15.4%). Knowledge of RFs was not significantly associated with BMI and WHR. Significantly, more respondents with tertiary education (18.6%) had high knowledge of HIs of obesity than those with primary education (3.1%). Prevalence of obesity was higher among respondents who had ever given birth (26.0%) than those who had not (7.5%). Respondents aged 30-34 years were more likely to have higher knowledge of RFs of obesity than those aged 15-19 years (OR: 2.6; 95%CI: 1.3–5.2). Respondents aged 40-44 years were more likely to have high WHR than those aged 15-19 years (OR: 14.6; 95%CI: 4.7-44.7). Women‘s knowledge of health implications of obesity was low despite their high knowledge of its risk factors. Community-based health education on health implications of obesity should be organised regularly for women of reproductive age in the study area.